Online correlates of cyberhate involvement among young people from ten European countries: An application of the Routine Activity and Problem Behaviour Theory. (October 2021) - Wachs, Sebastian; Mazzone, Angela; Milosevic, Tijana; Wright, Michelle F.; Blaya, Catherine; Gámez-Guadix, Manuel; O'Higgins Norman, James
Abstract: Recent evidence shows that young people across Europe are encountering hateful content on the Internet. However, there is a lack of empirically tested theories and investigation of correlates that could help to understand young people's involvement in cyberhate. To fill this gap, the present study aims to test the Routine Activity Theory to explain cyberhate victimisation and the Problem Behaviour Theory to understand cyberhate perpetration. Participants were 5433 young people ( M age  = 14.12, SD age  = 1.38; 49.8% boys from ten countries of the EU Kids Online IV survey). Self-report questionnaires were administered to assess cyberhate involvement, experiences of data misuse, frequency of contact with unknown people online, problematic aspects of sharenting, excessive Internet use, and sensation seeking. Results showed that being a victim of cyberhate was positively associated with target suitability (e.g., experiences of data misuse, and contact with unknown people), lack of capable guardianship (e.g., problematic facets of sharenting), and exposure to potential offenders (e.g., witnessing cyberhate, and excessive Internet use). Findings support the general usefulness of using Routine Activity Theory to explain cyberhate victimisation. Being a perpetrator of cyberhate was positively associated with several online problem behaviours (e.g., having contact with unknown people online, excessive Internet use, and sensation seeking), which supports the general assumption of the Problem Behaviour Theory. The findings of this research can be used to develop intervention and prevention programmes on a local, national, and international level. Highlights: This study investigates cyberhate among 5433 young people across ten countries. Several online correlates of cyberhate involvement will be reported. Being a cyberhate victim can be explained by the Routine Activity Theory. Being a cyberhate perpetrator can be explained by the Problem Behaviour Theory. Evidence-based prevention programmes to protect young people are needed.